Pharmacology activities and extraction of α-chitin prepared from crustaceans: A review - Renny Amelia&, Nyi Mekar Saptarini, Eli Halimah, Yuli Andriani, Aliya Nurhasanah, Jutti Levita, Sri Adi Sumiwi (Journal of Applied Pharmaceutical Science, 2020)
Most crustacean shells are not utilized and are discarded to become waste. α-Chitin, a polysaccharide compound, is commonly found in crustaceans shells. This polysaccharide is widely used in agriculture, pharmacy, and industry. Our review aims to add insights into various methods for extracting chitin from crustaceans. Besides, the pharmacological activities of α-chitin are also discussed in this article. The method of finding data was sourced from PubMed with predetermined criteria. From the article search, it was obtained that there are several ways to extract α-chitin from crustaceans, namely the chemical method, the microbiological method, and the combination of the chemical and enzymatic methods. The pharmacology activities of α-chitin from crustaceans, in general, revealed its potential to be developed as anticancer and anti-inflammatory and to accelerate wound healing.
Keywords: α-chitin, extraction, anti-inflammatory, anticancer, NADES, crab, glucosamine, marine.